Determination of Behavioral Finance Patterns Affecting Investors’ Activity in Capital Markets - Rothman, Tiran (Insights into Economics and Management Vol. 8, 2021)
Research by cognitive psychologists is challenging the rationality paradigm. It has started to penetrate economic modeling with a vast experimental documentation of cognitive limitations that has been accumulated so far raising the questions: Does behavioral decision models, which capture hope or expectation to risk in experimental settings, can help us comprehend investor behavior in financial markets. We try to portrait a whole picture on the attention hypothesis we have developed around pricing patterns within the innovative pharmaceuticals sector firms. We try to encompass it from several aspects: first, we lay a general psychological framework for Attention theory describing cognitive mechanisms such as the rule of selective attention in processing information in short-term. Second we explore financial aspects of selective attention, and last we explore real life investors` behavior around a major milestone within the drug development process – advisory committee milestone. Our findings, along with low interest rate in current world markets, lead to market optimism in this high risk sector. It is based on 78 events dating for 2002-2014, a puzzling investors` behavior. We observe that higher trading is held around regulatory event in what seems like a speculative “micro bubbles”. In this paper, we try to portrait a whole picture on the attention hypothesis and merge it with these “micro bubbles” we assume to be in the drug development industry.